Tradisi Ro’an (Kerja Bakti) dalam Meningkatkan Karakter Sosial Santri di Pondok Pesantren Al-Qomar Wahid Patianrowo Nganjuk - Mukhamat Saini (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
The ro'an (community service) tradition in the Al-qomar Wahid boarding school plays a role in shaping the character of the students. Tradition is a habit that has been taught from generation to generation and is still being carried out, one of which is the ro'an (community service) activity that has been carried out in the Al-qomar Wahid Islamic boarding school since it was first established. Ro'an (community service) is an activity that students cannot let go of, because it has become something that must be done and ro'an (community service) itself is an activity concerning cleanliness. If the environment is clean, the students will also feel comfortable regardless of the circumstances. This research uses qualitative research with the type of case studies, the data collection methods used are observation, interviews and documentation. Data analysis techniques in this study were data collection, data reduction, data presentation, conclusion and verification. Data validity checks using credibility, transferability, dependability and confirmability. The conclusions of the results of this study are first, that the ro'an (community service) tradition in the Al-qomar Wahid Islamic boarding school is very important, in order to form the social character of the students. Second, the character of students at the Al-qomar Wahid Islamic boarding school before carrying out ro'an (community service) activities is still individualistic, but the social character is awakened when the students finish doing ro'an (community service) activities which are carried out every week and even every day. with togetherness between friends. Third, the role of the ro'an tradition (community service) in enhancing the social character of the students at the Al-qomar Wahid Islamic boarding school is able to improve the social character of the students, such as the attitude of help, cooperation, tolerance, respect and respect for others and to have a sense of care or solidarity with others.